The Armadillo, Cabassous centralis (Cingulata: Chlamyphoridae) in a Costa Rican coffee agro-ecosystem (UNED Research Journal, 2019)
Introduction: The rare Cabassous centralis armadillo is classified as a Data Deficient species found from Mexico to northern South America). Objective: To expand the ecological distribution of C. centralis. Methods: We placed four trap cameras in strategic sites such as food sites, burrows, bodies of water and transition to the secondary forest, in San Ramón, Costa Rica. Results: We obtained a record of C. centralis in the transition between coffee plantation and secondary forest. Conclusion: This new finding near a coffee plantation adds to the list of habitats it occupies and can help in its conservation.
Keywords: agroecosystems; nked-tailed armadillo; Cingulata; coffee crops; armadillo